HO CHI MINH’S THOUGHT ON CULTURE - POLITICAL FOUNDATION FOR THE STRATEGY OF CULTURAL TOURISM DEVELOPMENT IN VIETNAM - Vinh, Nguyen Quang (Journal of Ecohumanism, 2024)
President Ho Chi Minh was honored by the United Nations Educational, Scientific and Cultural Organization (UNESCO) as a world cultural figure; a great leader and national liberation hero of Vietnam. For the Vietnamese state and people, Ho Chi Minh’s thought is a valuable asset and the foundation for the nation’s political direction. In the field of culture, Ho Chi Minh’s thought clearly demonstrates the content of developing an advanced Vietnamese culture, rich in national identity, creating momentum for the country’s economic and social development, including cultural tourism – one of Vietnam’s advantages in developing the tourism economy. This study analyzes the content of Ho Chi Minh’s thought on culture as the political basis for implementing the strategy of developing cultural tourism; and its application in cultural management to promote the development of cultural tourism in Vietnam. Based on the established theoretical framework, the author surveyed the opinions of 390 managers from 130 cultural and tourism organizations in several localities in Vietnam, including Hai Phong City (Northern), Da Nang City (Central), and Can Tho City (Southern). Based on the objective analysis and evaluation of the survey results, the author draws research conclusions and discusses policy issues aimed at achieving sustainable cultural and cultural tourism development in Vietnam.